Guggal: an important medicinal plant - Biswas, Shomita; Balakrishnan, Padmapriya; Tyagi, Kavita (Indian Horticulture, 2019)
Realizing the importance of guggal gum as a remedy for a large number of ailments and diseases, and its limited production and demand, NMPB, New Delhi, has supported several projects for its cultivation and conservation in various states of India. The NMPB has also supported a network as well as independent research projects on various aspects like survey, documentation, distribution map, collection of germplasm, tissue culture, nondestructive harvesting, seed/shoot germination and its standardization, identification of improved cultivars/stocks etc. Most recently of project on development, seed production areas and development of haploid plants of guggal has also been supported.